1979
DOI: 10.1111/j.1365-2125.1979.tb04776.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term treatment of hypertension with labetalol.

Abstract: 1 Thirty-two hypertensive patients have been treated with labetalol for periods of up to 7 years. 2 Ten patients observed for 6 years from the time of stabilization of dosage, did not show any tolerance to labetalol. 3 Postural and exercise hypotension were not seen in these patients over this prolonged follow-up, although they were seen in other patients given over 2 g labetalol daily.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
1

Year Published

1979
1979
1986
1986

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 2 publications
(2 reference statements)
4
22
1
Order By: Relevance
“…Labetalol has been used in combination with diuretics since the earliest clinical studies (Prichard & Boakes, 1976;Bolli et al, 1976).…”
Section: Labetalol and Diureticsmentioning
confidence: 99%
“…Labetalol has been used in combination with diuretics since the earliest clinical studies (Prichard & Boakes, 1976;Bolli et al, 1976).…”
Section: Labetalol and Diureticsmentioning
confidence: 99%
“…It was anticipated that this mechanism of action would cause excessive falls of blood pressure on standing or exercise by comparison with lying determinations, as seen with adrenergic-neurone blocking drugs (Prichard, Johnston, Hill & Rosenheim, 1968) or combined administration of potent a-and #-blocking adrenoceptor drugs such as phenoxybenzamine and propranolol (Beilin & Juel-Jensen, 1972). However, Prichard & Boakes (1976) reported that postural exacerbation of blood pressure reduction occurred only with doses of labetalol in excess of 1.8 g daily. By contrast other early reports (Pugsley, Armstrong, Nassim & Berlin, 1976;Bolli, Waal-Manning, Wood & Simpson, 1976) suggested that in patients previously treated with diuretics, smaller doses of labetalol showed increased anti-hypertensive effects on standing or after exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a study was designed to determine the effects of combination treatment with labetalol and a diuretic, and to compare them with those of each individual drug. As postural exacerbation of blood pressure was reported by Prichard & Boakes (1976) to be dose related, two dose levels of labetalol were studied.…”
Section: Introductionmentioning
confidence: 99%
“…In animal and human studies this drug has been found to decrease systemic vascular resistance and, thus, arterial blood pressure, only moderately slowing down heart rate (Brittain & Levy, 1976; Richards, 1976;Koch, 1977;Mehta & Cohn, 1977). Labetalol has been successfully used in the treatment of hypertension (Mehta & Cohn, 1977;Frick & Porsti, 1976;Prichard & Boakes, 1976); however, for the reasons mentioned above, it is conceivable that this drug could be beneficial also in coronary artery disease, independent of its anti-hypertensive action.…”
Section: Introductionmentioning
confidence: 99%